Reversal of New Onset Type 1 Diabetes by Oral Salmonella-Based Combination Therapy and Mediated by Regulatory T-Cells in NOD Mice - Mbongue, Jacques C.; Rawson, Jeffrey; Garcia, Pablo A.; Gonzalez, Nelson; Cobb, Jacob; Kandeel, Fouad; Ferreri, Kevin; Husseiny, Mohamed I. (Frontiers in Immunology, 2019)
Autoimmune diseases such as type 1 diabetes (T1D) involve the loss of regulatory mechanisms resulting in increased tissue-specific cytotoxicity. The result is destruction of pancreatic insulin-producing β-cells and loss of glucose homeostasis. We are developing a novel oral vaccine using live attenuated Salmonella to deliver TGFβ, IL10, and the diabetic autoantigen preproinsulin combined with low-doses of anti-CD3 mAb. Here we show that oral administration of Salmonella-based anti-CD3 mAb combined therapy reverses new-onset T1D in non-obese diabetic (NOD) mice. The therapeutic effect of the combined therapy was associated with induction of immune suppressive CD4+CD25+Foxp3+ Treg and CD4+CD49b+LAG3+ Tr1 cells. In adoptive transfer experiments, adding or depleting Treg or Tr1 cells indicated that both are important for preventing diabetes in combined therapy-treated mice, but that Tr1 cells may have a more central role. Furthermore induced Tr1 cells were found to be antigen-specific responding to peptide stimulation by secreting tolerance inducing IL10. These preclinical data demonstrate a role for Treg and Tr1 cells in combined therapy-mediated induction of tolerance in NOD mice. These results also demonstrate the potential of oral Salmonella-based combined therapy in the treatment of early T1D.